2017
DOI: 10.1002/anie.201708505
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Effects on Group Migration via a Rhodium(V) Nitrenoid Intermediate

Abstract: An unprecedented rhodium(III)-catalyzed hydroarylation of α,α-difluoromethylene alkynes with N-pivaloxyl aroylamides through sequential C-H activation and aryl migration is detailed herein. A large array of α,α-difluoromethylene alkynes and N-pivaloxyl aryl amides were amenable to this transformation, thus providing a novel synthetic protocol for the construction of difluorinated 2-alkenyl aniline derivatives in high yields and with excellent regioselectivity. Notably, unique fluorine effects were found to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 77 publications
2
37
0
Order By: Relevance
“…To determine the order of the Lossen rearrangement and the carbene migratory insertion, 1 na was subjected to the standard reaction condition with several nucleophiles such as methanol and aniline instead of 2 a , which, however, resulted in no Lossen rearrangement/nucleophilic addition product, but only in recovery of the starting materials (Scheme E). This result indicated that pathway B might be more favorable, and is also consistent with previous reports by the groups of Feng and Tanaka …”
Section: Methodssupporting
confidence: 92%
“…To determine the order of the Lossen rearrangement and the carbene migratory insertion, 1 na was subjected to the standard reaction condition with several nucleophiles such as methanol and aniline instead of 2 a , which, however, resulted in no Lossen rearrangement/nucleophilic addition product, but only in recovery of the starting materials (Scheme E). This result indicated that pathway B might be more favorable, and is also consistent with previous reports by the groups of Feng and Tanaka …”
Section: Methodssupporting
confidence: 92%
“…Addition of MeOH furnishes rhodacycle D , and subsequent reductive elimination affords 4 aa and the Cp A Rh I complex, which is oxidized by air to regenerate the Cp A Rh III complex. DFT calculation supports the formal Lossen rearrangement via a nitrene intermediate as shown in the Supporting Information (Scheme S1) . Alternatively, the pathway via rhodacycles E and F is also capable of affording 4 aa .…”
Section: Methodsmentioning
confidence: 80%
“…The Xu and Liu groups reported that in the intramolecular reactions of anilides with alkynes, reductive elimination proceeds to give an annulation product when using an electron‐rich alkyne, but protonation proceeds to give an alkenylation product when using an electron‐deficient alkyne (Scheme b) . The groups of Loh and Feng reported that in the [4+2] annulation of N ‐acyloxybenzamides with internal alkynes, not reductive elimination but β‐fluorine elimination or protonation proceeds to give [4+1] annulation or alkenylation products when using difluorinated internal alkynes (Scheme c). In these Cp*Rh III ‐catalyzed C−H bond‐functionalization reactions, substrate structures deter direct reductive elimination from rhodacycle intermediates.…”
Section: Introductionmentioning
confidence: 99%